2019
DOI: 10.1016/j.gie.2019.04.219
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of dye-based chromoendoscopy compared with standard- and high-definition white-light endoscopy in patients with inflammatory bowel disease at increased risk of colon cancer

Abstract: Background: Patients with ulcerative colitis have an increased risk of colorectal cancer. We sought to assess the comparative efficacy of standard white-light endoscopy (SDWLE) or high-definition white-light endoscopy (HDWLE) versus dye-based chromoendoscopy through a meta-analysis and rate the quality of evidence using the GRADE (Grading of Recommendations Assessment, Development, and Evaluation) system. Methods: A systematic review of the literature in PubMed, EMBASE, and Web of Science was performed in Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 41 publications
2
64
0
1
Order By: Relevance
“…(5) .027 Patients with advanced adenoma, n (%) 6 (4) 3 (2) .305 6 (5) 3 (2) .314 Patients with dysplasia in random biopsies, n (%) 6 (4) 3 (2) .305 6 (5) 3 (2) .479 Patients with all types of dysplasia, n (%) 21 (14) 9 (6) .020 19 (14) 8 (6) .027 Colorectal cancer 0 0 NA 0 0 NA Macroscopic lesions/10 min of withdrawal time, n 0 Previous research found that CE was superior to WLE in the detection of dysplasia in IBD when using standard resolution endoscopes. 6,7 Our results support that this is also the case when using HD endoscopes. In 2 recent meta-analysis 6,7 that included 3 randomized controlled studies, [12][13][14][15] HD-CE was compared with HD-WLE in subgroup analysis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…(5) .027 Patients with advanced adenoma, n (%) 6 (4) 3 (2) .305 6 (5) 3 (2) .314 Patients with dysplasia in random biopsies, n (%) 6 (4) 3 (2) .305 6 (5) 3 (2) .479 Patients with all types of dysplasia, n (%) 21 (14) 9 (6) .020 19 (14) 8 (6) .027 Colorectal cancer 0 0 NA 0 0 NA Macroscopic lesions/10 min of withdrawal time, n 0 Previous research found that CE was superior to WLE in the detection of dysplasia in IBD when using standard resolution endoscopes. 6,7 Our results support that this is also the case when using HD endoscopes. In 2 recent meta-analysis 6,7 that included 3 randomized controlled studies, [12][13][14][15] HD-CE was compared with HD-WLE in subgroup analysis.…”
Section: Discussionsupporting
confidence: 82%
“…[3][4][5] Two recent meta-analysis reported a higher likelihood of detecting patients with dysplasia with CE as compared with white light endoscopy (WLE), but subgroup analyses confirmed this finding only when CE was compared with standard-definition WLE. 6,7 Thus, the evidence in support of CE using high-definition (HD) endoscopes is weak.…”
mentioning
confidence: 99%
“…Rather, subgroup analyses focus on the difference in the effect of the intervention between the subgroups: eg, is the increase in detection of dysplasia with chromoendoscopy versus SDWLE significantly different from the increase with chromoendoscopy versus HDWLE? [2][3][4] In the study by Feuerstein et al, 1 the test for subgroup difference P value was 0.26. Therefore, the detection of dysplasia with chromoendoscopy versus SDWLE is not significantly different from the detection with chromoendoscopy versus HDWLE.…”
Section: Chromoendoscopy Meta-analysis: Correcting Subgroup Analysis mentioning
confidence: 99%
“…We appreciate the interest and comments from Laine et al, 1 but we would like to highlight that none of our results were a subgroup analysis 1. In the methods, we noted that we performed a primary analysis comparing standard-definition white-light endoscopy (SDWLE) with chromoendoscopy and high-definition white-light endoscopy (HDWLE) with chromoendoscopy 2.…”
mentioning
confidence: 95%
“…A recent meta-analysis of 10 studies (494 patients) compared dye-based chromoendoscopy with standard-definition WLE and high-definition WLE 7 . RCTs in the literature showed a small benefit of chromoendoscopy over standard-definition WLE, but not over high-definition WLE.…”
mentioning
confidence: 99%